How toxic is the COVID-19 drug azithromycin in the presence of Posidonia oceanica? Toxicokinetics and experimental approach of meiobenthic nematodes from a metallically pristine area. (15th February 2023) - Badraoui, Riadh; Mannai, Ghofrane; Siddiqui, Arif J.; Pacioglu, Octavian; Rudayni, Hassan A.; Boufahja, Fehmi; Essid, Naceur
Abstract: The current study presents the results of an experiment carried to assess the impact of azithromycin, a COVID-19 drug, probably accumulated in marine sediments for three years, since the start of the pandemic, on benthic marine nematodes. It was explored the extent to which a common macrophyte from the Mediterranean Sea influenced the toxic impact of azithromycin on meiobenthic nematodes. Metals are known to influence toxicity of azithromycin. The nematofauna from a metallically pristine site situated in Bizerte bay, Tunisia, was exposed to two concentrations of azithromycin [i.e. 5 and 10 μg l −1 ]. In addition, two masses of the common macrophyte Posidonia oceanica [10 and 20% Dry Weight (DW)] were considered and associated with azithromycin into four possible combinations. The abundance and the taxonomic diversity of the nematode communities decreased significantly following the exposure to azithromycin, which was confirmed by the toxicokinetic data and behaving as substrate for P-glycoprotein (P-gp). The toxicity of 5 μg l −1 dosage of azithromycin was partially reduced at 10% DW of Posidonia and completely at 20% DW. The results showed that 5 μg l −1 of azithromycin can be reduced by the macrophyte P. oceanica when present in the environment at low masses as 10% DW. Graphical abstract: Image 1 Highlights: Abundance and diversity of nematodes decreased in presence of azithromycin. Posidonia oceanica did not have any meaningful impact on nematode diversity. Toxicity of 5 μg azithromycin. l −1 was neutralized at 20% Dry Weight of Posidonia .